2007
DOI: 10.1021/ma0710028
|View full text |Cite
|
Sign up to set email alerts
|

Sheetlike Side-Chain Liquid Crystalline Polyacetylenes Forming Monolayer Lamellae in Dilute Solutions

Abstract: Self-assembly behaviors of a series of hydrophobic side-chain liquid crystalline (LC) polyacetylenes, namely, poly(5-{[(4‘-alkoxy-4-biphenylyl)carbonyl]oxy}-1-pentyne)s [P-3,m (m = 5, 7, 9)], were studied in dilute solutions. The assembly was induced by tuning the solvent property to be selective for the alkyl tails on the side chains, with the processes characterized by turbidity, dynamic light scattering, 1H NMR, and excitation fluorescence anisotropy measurements. The morphology and structure of the P-3,m a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The introduction of liquid-crystalline pendants to the conjugated polyacetylene backbones has attracted much attention because the resulting offspring may be both light emitting and liquid crystalline, which may offer an array of exciting opportunities for high-tech innovations. [12][13][14] Although the disubstituted (RC=CR') n polymers have been reported to exhibit higher thermal stability, higher glass transition temperatures and higher luminescence efficiency than monosubstituted polymers (CH=CR) n , the latter are studied much more because they can be polymerized easier. 12 Our research team has synthesised several monomers of polyacetylene containing triphenylene.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of liquid-crystalline pendants to the conjugated polyacetylene backbones has attracted much attention because the resulting offspring may be both light emitting and liquid crystalline, which may offer an array of exciting opportunities for high-tech innovations. [12][13][14] Although the disubstituted (RC=CR') n polymers have been reported to exhibit higher thermal stability, higher glass transition temperatures and higher luminescence efficiency than monosubstituted polymers (CH=CR) n , the latter are studied much more because they can be polymerized easier. 12 Our research team has synthesised several monomers of polyacetylene containing triphenylene.…”
Section: Introductionmentioning
confidence: 99%
“…These sheet-like side chain LC PAs can form monolayer lamellae in dilute solution. 37 The mono-substituted PAs bearing ferroelectric LC groups can also show chiral nematic and smectic phases under LC state. 38 In addition to PAs, many other conjugated polymers incorporating with LC side groups have also been synthesized and characterized.…”
Section: Side-chain Lc Conjugated Polymersmentioning
confidence: 99%
“…Later on, we found that this sheet-like SCLCPA, in solvents selective for the alkyl tails, can selfassemble into monolayer lamellae with thickness nearly identical to the molecular width. [76] In order to form an LC phase using the building block of the whole sheet-like SCLCPA molecules rather than only the side-chains, one may intuitively consider that the flexible spacer is not necessary. The rigid mesogenic moieties can be directly linked to the PA backbone without spacer.…”
Section: Sheet-like Mspas and Their Smectic Lc Phasesmentioning
confidence: 99%